-2(y-5)=6(y+5)-12

Simple and best practice solution for -2(y-5)=6(y+5)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(y-5)=6(y+5)-12 equation:



-2(y-5)=6(y+5)-12
We move all terms to the left:
-2(y-5)-(6(y+5)-12)=0
We multiply parentheses
-2y-(6(y+5)-12)+10=0
We calculate terms in parentheses: -(6(y+5)-12), so:
6(y+5)-12
We multiply parentheses
6y+30-12
We add all the numbers together, and all the variables
6y+18
Back to the equation:
-(6y+18)
We get rid of parentheses
-2y-6y-18+10=0
We add all the numbers together, and all the variables
-8y-8=0
We move all terms containing y to the left, all other terms to the right
-8y=8
y=8/-8
y=-1

See similar equations:

| 4(t-4)+8=4(2t-5) | | 6n=3n+8 | | -16/4=-3(6z) | | 8n=7n+9 | | 11+m=19 | | 9a+10=-44 | | 4x+10°=180 | | x(40(1.18))=65 | | (40(1.18))x=65 | | x+10°+3x=180 | | 14-2y=22 | | 8x+24=4 | | 5(x+2)=26-3x | | 4x+4x-13=0 | | x+14-8x=0 | | 25^3-3x=5^-8x | | 5(m+1)=(7m-1) | | 2x-5(x+6)=35+5x | | 2a+4=a=6 | | 1/2x-3/4=6x+3 | | 24-6f=-5 | | 5^7x-3=625 | | 3/4(1/4x+8)-(1/2+2)=3/8(4-x)-1/4x | | 3x2+10=1 | | 5(2n+3)-5=70 | | |10x-33|=7x | | x=23=92 | | 44.58+y=144.05 | | 44.58=y=144.05 | | x*3=85 | | (x+2)(x+3)=x+11 | | (x-1)2=-2(x-5) |

Equations solver categories